Diversity and population connectivity of members of the family Eunicidae inhabiting deep-water corals in the North Atlantic - Carlota Gracia-Sancha; Nicolai Roterman; Michelle L. Taylor; Kerry L. Howell; Alex D. Rogers; Sofía Ruiz-Cano; Sergi Taboada (Molecular Phylogenetics and Evolution, 2026)

Editorial – Foreword - Kerry Howell; Ana Hilario (Progress in Oceanography, 2026)

Ecological Benthic Units: A New Characterization of the Global Seafloor for Ocean Spatial Planning and Management - Peter Harris; Dawn Wright; Kevin Butler; Keith VanGraafeiland; Mark Costello; Kerry Howell; Gustav Kågesten; Vanessa Lucieer; Miles Macmillan-Lawler; Roger Sayre (Oceanography, 2026)
Effective management of deep-sea ecosystems and the high seas is hindered by the absence of a globally consistent framework for characterizing benthic habitats. Here we present the first global ecological classification of the seafloor, comprising 250 unique ecological benthic units (EBUs), distributed on the seafloor as nearly 700,000 EBU polygon occurrences, generated by intersecting a high-resolution geomorphic map with multivariate environmental seascapes. Using 17 million seafloor data points and 0.05° resolution biophysical datasets—including bottom temperature, dissolved oxygen, pH, carbon flux, sediment thickness, crustal age, and bottom currents—we identified 57 benthic regions across six major geomorphic groups (shelves, slopes, seamounts/guyots, spreading ridges, abyssal/hadal areas, plateaus). The resulting EBUs reveal previously unrecognized ecological gradients, quantify global patterns of benthic heterogeneity, and expose large-scale environmental vulnerabilities. Notably, we find that 95.6 million km2 (26% of the ocean area) of abyssal seafloor lies below the carbonate compensation depth, that 4.16 million km2 (1% of the ocean) of continental slopes intersect severe oxygen minima, and

Deep-sea ecosystems of the North Atlantic Ocean: discovery, status, function and future challenges - A. Louise Allcock; Diva J. Amon; Amelia E.H. Bridges; Ana Colaço; Elva Escobar-Briones; Ana Hilário; Kerry L. Howell; Nélia C. Mestre; Frank E. Muller-Karger; Imants G. Priede; Paul V.R. Snelgrove; Kathleen Sullivan Sealey; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Licence to predict – Investigating approaches to modelling low-occurrence deep-sea Irish Antipatharia with a new evaluation metric - ALEXA PARIMBELLI; MARK P. JOHNSON; KERRY HOWELL; CLAIRE LAGUIONIE-MARCHAIS; A. LOUISE ALLCOCK (Mediterranean Marine Science, 2025)
Species distribution modelling has proven effective in locating cold-water coral hotspots in the deep sea. Maximum entropy (MaxEnt) and gradient boosting (GBM) are equally good at modelling rare species, but previous efforts to predict the distribution of deep-sea Antipatharia have mostly employed MaxEnt. This study investigates how algorithm choice (MaxEnt or GBM) and the application of backward stepwise variable pre-selection influence model performance and generalisation. Thirty-six models (four frameworks for nine black coral morphospecies) were built and evaluated using AUC, TSS, and the average TSS index (ATI), a novel metric that calculates TSS drops between training and test data to measure generalisation capability.ATI identified concerns in model generalisation that were not captured by AUC and TSS, making it a valuable tool for evaluating predictive model quality in conservation applications. MaxEnt outperformed GBM in predicting black coral distribution, and the pre-selection of variables did not improve performance. Satisfactory results were only obtained for the two MaxEnt models of Stichopathes gravieri, providing insights into the implications of using small datasets in conservation efforts. The inconsistencies in our findings do not lead us to recommend the use of a single model type in future studies; rather, we stress the importance of careful evaluation of model metrics with ecological knowledge of the species distribution when applying a dataset to conservation purposes.

Blue carbon in an eastern boundary upwelling zone – A case study in Namibia - Simon H. Elwen; Usman Khan; Anja Kreiner; Anja K. Van der Plas; Margit R. Wilhelm; David Barnes; Kerry Howell; Tara Pelembe (Deep Sea Research Part II: Topical Studies in Oceanography, 2025)

A risk assessment for the remote ocean: the case of the South East Atlantic - Holly J. Niner; Siân E. Rees; Giulia La Bianca; Kirsty A. McQuaid; Kerry L. Howell (Frontiers in Marine Science, 2024)
Degradation of the natural world and associated ecosystem services is attributed to a historical failure to include its ‘value’ in decision-making. Uncertainty in the quantification of the relationship between natural capital ‘assets’ that give rise to critical societal benefits and people is one reason for the omission of these values from natural resource management. As this uncertainty increases in marine systems and further still with distance from the coast, the connection between society and natural capital assets is less likely to be included adequately in decision-making. Natural capital assets of Areas Beyond National Jurisdiction (ABNJ), including those of the deep sea, are distant but are known to generate many benefits for society, from the diffuse and broad-scale benefits of climate regulation to the provision of wild fish for food. While our understanding of the precise relationships (the status of asset stocks, ecosystem functions and processes) that control the availability of ecosystem services and the flows of benefits is limited, this does not preclude opening a discourse on how these natural capital assets could best be managed to continue to benefit society. Here we apply a natural capital approach to the South East Atlantic ABNJ, one of the least scientifically understood regions of the planet, and develop a framework for risk assessment. We do this by describing the benefit flows from the natural capital assets of the region, appraising how activities are creating pressures on these flows and whether the controls for these pressures protect them. Our risk register highlights how governance currently favours the protection of direct (extractive) benefit flows from natural capital assets of the region, which are primarily targeted for financial benefit. Without a systems-based framework that can account for the cumulative pressures on natural capital assets their status, associated ecosystem services and benefits are at risk. Such an approach is essential to capture and protect the foundational and often diffuse connections between marine natural capital and global society.

Filling the data gaps: Transferring models from data-rich to data-poor deep-sea areas to support spatial management - Amelia E.H. Bridges; David K.A. Barnes; James B. Bell; Rebecca E. Ross; Lizette Voges; Kerry L. Howell (Journal of Environmental Management, 2023)

Broad-scale benthic habitat classification of the South Atlantic - Kirsty A. McQuaid; Amelia E.H. Bridges; Kerry L. Howell; Tiago B.R. Gandra; Vitor de Souza; Jock C. Currie; Oliver T. Hogg; Tabitha R.R. Pearman; James B. Bell; Lara J. Atkinson; Diane Baum; Jarbas Bonetti; et al. (Progress in Oceanography, 2023)

A standardised ecosystem services framework for the deep sea - Giulia La Bianca; Sian Rees; Martin J. Attrill; Amanda T. Lombard; Kirsty A. McQuaid; Holly J. Niner; Henk van Rein; Kerry J. Sink; Kerry L. Howell (Frontiers in Marine Science, 2023)
Despite its remoteness, human activity has impacted the deep sea and changes to the structure and function of deep-sea ecosystems are already noticeable. In terrestrial and shallow water marine environments, demonstrating how ecosystems support human well-being has been instrumental in setting policy and management objectives for sustainable resource use. Foundational to this approach is a framework of ecosystem service (ES) classification and a synthesis of the knowledge base, which can then be used to structure decision-support tools such as ecosystem accounts or Environmental Impact Assessments. At present, no such framework exists for the deep sea. There is thus an urgent need to determine and assess the ES provided by deep-sea habitats and species before (potentially irreversible) decisions are made about deep-sea habitat use and governance. As a first step towards the incorporation of ES in such decision-making, we undertake two systematic reviews of the scientific literature based on the principles of the Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) systematic process. This was to define a comparative ES framework and synthesise the current evidence base for how deep-sea habitats support ecosystem services. Our framework proposes four supporting services, three regulating services, four provisioning services and three cultural services for which there is an established and growing body of evidence for the role of deep-sea habitats. The ES framework presented here provides a structure for deep-sea ecosystem services. In its next phase of development, this could provide the foundation for the development of habitat-ecosystem service matrices, which are a critical component for truly accounting for ES in decision-making, particularly spatial management. This framework has significant implications for deep-sea management, conservation and policy, as it provides an ecosystem services-based tool that can be used in any deep-sea ecosystems management across the planet, and it also shows how critical these data gaps are for today’s decisions and how seriously they should be considered in decision-making processes.

Integrated ecosystem assessment around islands of the tropical South Mid-Atlantic Ridge - Amanda R. Rodrigues; Sergio R. Floeter; Vicente Gomes; Débora S. Ferrari; Vinicius J. Giglio; Fernanda C. Silva; Ana M. R. Liedke; Carlos E. L. Ferreira; Kerry Howell; Maria A. Gasalla (Frontiers in Marine Science, 2023)
The South Mid Atlantic Ridge comprises three main oceanic islands in the equatorial and tropical portions of the Atlantic Ocean. These islands are isolated from each other and equidistant from both the continental margins of South America and Africa, sharing common patterns but with different types of human use and pressures. Moreover, the areas beyond national jurisdiction between those islands are visited and exploited by distant fishing fleets and include large areas of shipping activity for commodities. Here, a pioneering integrated ecosystem assessment (IEA) process is constructed for the region among Saint Peter and Saint Paul’s Archipelago (Brazil), Saint Helena Island and Ascension Island (UK overseas territories). For that, we used a qualitative assessment of risks arising from anthropogenic activities, representing a novel contribution to the field. The Options for Delivering Ecosystem-Based Marine Management (ODEMM) approach was applied to trace sector–pressure–component pathways. A ‘linkage framework’ was outlined including pressures affecting each ecosystem component, and supported a process of knowledge attributions that scored the impact risks. All results were validated with regional stakeholders through workshops, including local and international management bodies, non-governmental organizations (NGOs) and scientists. The approach focused on a significant area among encompassing the open ocean, shallow and deep-sea biomes, analyzing the main sectors and pressures affecting the ecological components. Our results identified 14 sectors and 16 key pressures associated with 23 ecosystem components, totaling 780 impact chains. Fishing, shipping, wastewater, and tourism/recreation appeared as the top impacting sectors. Fishing and shipping were the most connected with ecosystem components links. Litter, species extraction, contaminants, and bycatch were the pressures that had the highest risk of impact values. Lastly, demersal and pelagic fish and pelagic and demersal elasmobranchs were the groups with the highest risk related to overall impacts, which were supported by local and regional evidence from long term monitoring programs and local studies. Our study demonstrated that these seemingly pristine islands and oceanic waters are already experiencing human impacts that should be addressed by local both conservation measures and international agreements. We also highlight the pressures that should be prioritized for better monitoring and policy, as well as those linkage components that have been less investigated.

Oceanographic variability drives the distribution but not the density of the aggregation forming deep-sea sponge Pheronema carpenteri - Kyran P. Graves; Amelia E.H. Bridges; Tomasz Dabrowski; Thomas Furey; Kieran Lyons; Kerry L. Howell (Deep Sea Research Part I: Oceanographic Research Papers, 2023)

Depth and latitudinal gradients of diversity in seamount benthic communities - Amelia E. H. Bridges; David K. A. Barnes; James B. Bell; Rebecca E. Ross; Kerry L. Howell (Journal of Biogeography, 2022)
Aim Latitudinal and bathymetric species diversity gradients in the deep sea have been identified, but studies have rarely considered these gradients across hard substratum habitats, such as seamount and oceanic island margins. This study aimed to identify whether the current understanding of latitudinal and bathymetric gradients in α‐diversity (species richness) apply to seamount ecosystems, as well as ascertaining whether identifiable trends were present in seamount β‐diversity along a bathymetric gradient. Location Exclusive Economic Zones of Saint Helena, Ascension Island and Tristan da Cunha, spanning 8–40°S in the South Atlantic. Taxon Seamount megabenthic communities. Methods Images from 39 transects, collected between 250 and 950 m, were used to characterise species richness. We subsequently applied general linear models to test possible environmental drivers across latitudinal and bathymetric ranges. Regression models were employed to investigate the β‐diversity gradient of species turnover with depth. Results Transects in temperate latitude had significantly higher species richness than those in the tropics. Surface primary productivity and substrate hardness both had significant positive effects on species richness, and a weak relationship between temperature and species richness was observed. No significant relationship between species richness and depth was detected, but there was significant species turnover with depth. Main conclusions Seamounts and oceanic islands do not conform to established depth–diversity relationships within the depth range studied. However, seamounts and oceanic islands in the South Atlantic do appear to follow a parabolic latitudinal diversity gradient, closely associated with higher productivity in temperate regions.

Editorial: Biodiversity, Connectivity and Ecosystem Function Across the Clarion-Clipperton Zone: A Regional Synthesis for an Area Targeted for Nodule Mining - Craig R. Smith; Malcolm R. Clark; Erica Goetze; Adrian G. Glover; Kerry L. Howell (Frontiers in Marine Science, 2021)

Benthic Assemblage Composition of South Atlantic Seamounts - Amelia E. H. Bridges; David K. A. Barnes; James B. Bell; Rebecca E. Ross; Kerry L. Howell (Frontiers in Marine Science, 2021)
Seamounts and oceanic islands rise from the seafloor and provide suitable habitat for a diverse range of biological assemblages including Vulnerable Marine Ecosystems (VMEs). Whilst they have been the focus of some work globally, there has been little description of the biological and physical environments of seamounts in the South Atlantic Ocean. In this study, we characterized benthic assemblage composition from 13 seamounts and oceanic islands spanning 8–40°S within the exclusive economic zones (EEZs) of Ascension Island, Saint Helena and Tristan da Cunha. Drop camera imagery was collected between 170 and 1000 m. All fauna present in images were identified and quantified, and multivariate statistics were used to describe biological assemblages and identify their environmental drivers. Benthic communities of temperate regions (Tristan da Cunha archipelago) were shown to be distinct from those found in the tropics, with latitude and depth identified as key environmental drivers of assemblage composition. Our results are consistent with the current understanding of the biogeography of the South Atlantic, both in terms of the distinction between tropical and temperate regions, and the influence of depth and water mass structure on assemblage distribution. Faunal assemblages are similar to those observed in the North Atlantic in terms of functional groups. VMEs are present within the EEZs of all three territories and are potentially protected from some threats by large marine protected areas (MPAs). Our imagery, data and analyses provide a baseline for south Atlantic seamounts so that future monitoring can establish whether existing protected status is sufficient to conserve both unique biodiversity and considerable potential for vital ecosystem services.

Using Habitat Classification to Assess Representativity of a Protected Area Network in a Large, Data-Poor Area Targeted for Deep-Sea Mining - Kirsty A. McQuaid; Martin J. Attrill; Malcolm R. Clark; Amber Cobley; Adrian G. Glover; Craig R. Smith; Kerry L. Howell (Frontiers in Marine Science, 2020)
Extractive activities in the ocean are expanding into the vast, poorly studied deep sea, with the consequence that environmental management decisions must be made for data-poor seafloor regions. Habitat classification can support marine spatial planning and inform decision-making processes in such areas. We present a regional, top–down, broad-scale, seafloor-habitat classification for the Clarion-Clipperton Fracture Zone (CCZ), an area targeted for future polymetallic nodule mining in abyssal waters in the equatorial Pacific Ocean. Our classification uses non-hierarchical, k-medoids clustering to combine environmental correlates of faunal distributions in the region. The classification uses topographic variables, particulate organic carbon flux to the seafloor, and is the first to use nodule abundance as a habitat variable. Twenty-four habitat classes are identified, with large expanses of abyssal plain and smaller classes with varying topography, food supply, and substrata. We then assess habitat representativity of the current network of protected areas (called Areas of Particular Environmental Interest) in the CCZ. Several habitat classes with high nodule abundance are common in mining exploration claims, but currently receive little to no protection in APEIs. There are several large unmanaged areas containing high nodule abundance on the periphery of the CCZ, as well as smaller unmanaged areas within the central CCZ, that could be considered for protection from mining to improve habitat representativity and safeguard regional biodiversity.

A Blueprint for an Inclusive, Global Deep-Sea Ocean Decade Field Program - Kerry L. Howell; Ana Hilário; A. Louise Allcock; David M. Bailey; Maria Baker; Malcolm R. Clark; Ana Colaço; Jon Copley; Erik E. Cordes; Roberto Danovaro; Awantha Dissanayake; Elva Escobar; et al. (Frontiers in Marine Science, 2020)
The ocean plays a crucial role in the functioning of the Earth System and in the provision of vital goods and services. The United Nations (UN) declared 2021–2030 as the UN Decade of Ocean Science for Sustainable Development. The Roadmap for the Ocean Decade aims to achieve six critical societal outcomes (SOs) by 2030, through the pursuit of four objectives (Os). It specifically recognizes the scarcity of biological data for deep-sea biomes, and challenges the global scientific community to conduct research to advance understanding of deep-sea ecosystems to inform sustainable management. In this paper, we map four key scientific questions identified by the academic community to the Ocean Decade SOs: (i) What is the diversity of life in the deep ocean? (ii) How are populations and habitats connected? (iii) What is the role of living organisms in ecosystem function and service provision? and (iv) How do species, communities, and ecosystems respond to disturbance? We then consider the design of a global-scale program to address these questions by reviewing key drivers of ecological pattern and process. We recommend using the following criteria to stratify a global survey design: biogeographic region, depth, horizontal distance, substrate type, high and low climate hazard, fished/unfished, near/far from sources of pollution, licensed/protected from industry activities. We consider both spatial and temporal surveys, and emphasize new biological data collection that prioritizes southern and polar latitudes, deeper (> 2000 m) depths, and midwater environments. We provide guidance on observational, experimental, and monitoring needs for different benthic and pelagic ecosystems. We then review recent efforts to standardize biological data and specimen collection and archiving, making “sampling design to knowledge application” recommendations in the context of a new global program. We also review and comment on needs, and recommend actions, to develop capacity in deep-sea research; and the role of inclusivity - from accessing indigenous and local knowledge to the sharing of technologies - as part of such a global program. We discuss the concept of a new global deep-sea biological research program ‘ Challenger 150 ,’ highlighting what it could deliver for the Ocean Decade and UN Sustainable Development Goal 14.

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Comparing Deep-Sea Larval Dispersal Models: A Cautionary Tale for Ecology and Conservation - Rebecca E. Ross; W. Alex M. Nimmo-Smith; Ricardo Torres; Kerry L. Howell (Frontiers in Marine Science, 2020)

Combining Distribution and Dispersal Models to Identify a Particularly Vulnerable Marine Ecosystem - Rebecca E. Ross; Edward J. G. Wort; Kerry L. Howell (Frontiers in Marine Science, 2019)

Modelling tidally induced larval dispersal over Anton Dohrn Seamount - Nataliya Stashchuk; Vasiliy Vlasenko; Kerry L. Howell (Ocean Dynamics, 2018)

A Multidisciplinary Approach for Generating Globally Consistent Data on Mesophotic, Deep-Pelagic, and Bathyal Biological Communities - Lucy Woodall; Dominic Andradi-Brown; Andrew Brierley; Malcolm Clark; Douglas Connelly; Rob Hall; Kerry Howell; Veerle Huvenne; Katrin Linse; Rebecca Ross; Paul Snelgrove; Paris Stefanoudis; et al. (Oceanography, 2018)

Ecological Role of Submarine Canyons and Need for Canyon Conservation: A Review - Ulla Fernandez-Arcaya; Eva Ramirez-Llodra; Jacopo Aguzzi; A. Louise Allcock; Jaime S. Davies; Awantha Dissanayake; Peter Harris; Kerry Howell; Veerle A. I. Huvenne; Miles Macmillan-Lawler; Jacobo Martín; Lenaick Menot; et al. (Frontiers in Marine Science, 2017)

Estimating dispersal distance in the deep sea: challenges and applications to marine reserves - Ana HilÃ¡rio; Anna Metaxas; Sylvie M. Gaudron; Kerry L. Howell; Annie Mercier; NÃ©lia C. Mestre; Rebecca E. Ross; Andreas M. Thurnherr; Craig Young (Frontiers in Marine Science, 2015)

Mounting evidence: near‐slope seamounts are faunally indistinct from an adjacent bank - Kerry L. Howell; Sophie L. Mowles; Andrew Foggo (Marine Ecology, 2010)
Seamounts have been described as island habitats harbouring a unique fauna, and as biodiversity hotspots with high rates of endemism. However, recent research suggests that these generalisations are inappropriate and poorly supported, though appropriate on and off seamount comparative data are lacking. This study uses quantitative data derived from video analysis to compare epibenthic megafaunal community composition, diversity and potential species endemism on two seamounts and one bank in the Rockall Trough region of the NE Atlantic. Sample data were standardised for substratum type across all three features and as far as possible for depth and geomorphological variation. The results suggest that under similar environmental conditions, e.g . similar substratum, depth and geomorphology, there is little difference between the communities of the bank and seamounts in the Rockall Trough. Where differences are observed, the ‘guyot’ seamount is as different to the conical seamount as it is to the bank. The seamounts are no more or less diverse than the bank; endemism is low or non‐existent. The results are discussed in the context of the common generalisations made concerning seamount communities and the implications for conservation and management of the deep sea.

Reproductive isolation among morphotypes of the Atlantic seastar species Zoroaster fulgens (Asteroidea: Echinodermata) - Kerry L. Howell; Alex D. Rogers; Paul A. Tyler; David S. M. Billett (Marine Biology, 2004)